Copper-Mediated Direct Aryloxylation of Benzamides Assisted by an N,O‑Bidentate Directing Group - Hao, Xin-Qi; Chen, Li-Juan; Ren, Baozeng; Li, Liu-Yan; Yang, Xin-Yan; Gong, Jun-Fang; Niu, Jun-Long; Song, Mao-Ping (Organic letters, 2014)
Copper-mediated selective mono- or diaryloxylation of benzamides has been achieved by using 2-aminopyridine 1-oxide as a new and removable N,O-bidentate directing group. The reaction system shows a broad substrate scope and provides a straightforward way for the synthesis of mono- and diaryloxylated benzoic acids.